Some properties of silica-supported nickel catalysts - Firer, Colin (Department of Chemistry, 2016)
A literature survey has been made of earlier work on factors which have been found to influence the catalytic activity of supported metal catalysts. In particular an interaction has been shown to exist between the metal and its support in these catalysts. Two of the important factors which were shown to affect activity are the average metal crystallite size and the fraction of the metal present in a non-metallic form (for example as metal ions) in the catalyst. The earlier work consists almost exclusively of kinetic studies of heterogeneously catalyzed reactions. It is suggested that the conclusions are of a limited value owing to the widespread existence of the compensation effect, the fact that different test reactions may give contrasting results as to the relative activities of a series of catalysts and the belief that only a small fraction of the surface sites of a catalyst is generally involved in a given heterogeneous reaction. The work described in this thesis consists of an investigation of the effects of various factors on the isosteric heat of adsorption of an adsorbate per unit metal area on supported metal catalysts. The heat of adsorption per unit metal area provides a measure of the strength of the bond between the adsorbate and the surface atoms of the adsorbent. It was felt that this approach would give further insight into the factors affecting catalytic activity because the disadvantages, mentioned above, of kinetic studies would be eliminated.